Oil-based rock debris-based fracturing propping agent and preparation method thereof

By using oil bedrock cuttings and low-grade bauxite to prepare fracturing proppants with carbon nanotube structures, the corrosion and performance degradation of fracturing proppants in the prior art under harsh environments is solved, and the effects of low density, high strength and high acid resistance are achieved, and production costs and energy consumption are reduced.

CN119899654APending Publication Date: 2025-04-29SINOPEC OILFIELD SERVICE CORPORATION +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411878964.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing fracturing proppants are prone to corrosion, powder loss or crushing under severe acid fracturing fluid and high closing pressure environments, resulting in a decrease in flow diversion capacity and reduced oil and gas production. At the same time, high viscosity sand carrying fluid increases production costs and damage to the reservoir.

Method used

Oil-bedded rock chips and low-grade bauxite are used as raw materials, and fracturing proppants with low-density, high-strength, and high acid-resistant carbon nanotube structure are generated through steps such as absorption oxygen calcination and vacuum ball milling.

Benefits of technology

It significantly improves the strength, hardness and acid resistance of the ceramic proppant, reduces density and production costs, and avoids energy consumption of oxidation reactions and high-temperature calcination, achieving more efficient oil and gas mining.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005197690130000081
    Figure BDA0005197690130000081
  • Figure BDA0005197690130000091
    Figure BDA0005197690130000091
Patent Text Reader

Abstract

The invention relates to the technical field of oil and gas exploitation, and discloses an oil-based rock debris-based fracturing propping agent and a preparation method thereof.The method comprises the steps that dried oil-based rock debris and bauxite are crushed respectively, sieved through a 60-mesh sieve and then mixed to obtain a mixture, and water is added into the mixture for granulation to obtain raw material balls; and calcining the raw material balls in a tubular furnace under an anaerobic condition, and cooling to obtain the fracturing propping agent. The fracturing propping agent is prepared by the method. The method disclosed by the invention is simple in process, low in energy consumption and low in production cost, and the prepared bedrock debris-based fracturing propping agent has the advantages of low density, high strength and high acid oil resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas exploitation, in particular to an oil-based rock cuttings-based fracturing proppant and a preparation method thereof. Background Art

[0002] Fracturing proppants are used in the exploitation of unconventional oil and gas reservoirs. Their role is to resist formation pressure to maintain the opening of high-conductivity fractures and ensure the conductivity of fractures to achieve the purpose of increasing production. Therefore, the performance of pressure proppants plays a very important role in the process of oil and gas production. During the operation of fracturing proppants, they will be subjected to the test of harsh environments for a long time, such as corrosion by acidic fracturing fluids and extremely high closure pressure of rock formations. If they do not have excellent acid and pressure resistance, the corroded fracturing proppants will become loose due to the corrosion of the medium in the working environment, causing structural failure. At the same time, the fracturing proppants will fall off or even break under high closure pressure. The fallen debris will be deposited between the gaps formed by the fracturing proppants, causing blockage of the flow channel, weakening the conductivity, and ultimately leading to a decrease in oil and gas production.

[0003] In recent years, high-grade bauxite has become popular as the main raw material for preparing high-strength ceramsite fracturing proppants. However, according to the principle of fracturing, the higher the strength of the proppant, the greater the density, and the greater the viscosity of the sand-carrying fluid required. High-viscosity sand-carrying fluid will add too much thickener and organic suspending agent to improve the sand-carrying capacity, resulting in increased costs and damage to the reservoir, shortening the service life of the gas reservoir, and increasing the demand for low-density proppant materials. However, as the density decreases, the strength decreases. In the application of proppant materials, it is necessary to reduce the density while ensuring the mechanical properties. In addition, the acid solubility of most ceramsite proppants on the market exceeds the relevant standard value. The acid solubility can be reduced by coating the proppant surface with resin, but it greatly increases the production cost. Therefore, the preparation of proppant materials with low density, high strength and high acid resistance is the future development trend.

[0004] Oil-based cuttings are a common hazardous waste generated during shale gas drilling and production, mainly composed of crushed rock cuttings, waste oil-based drilling fluid and underground wastewater. Using oil-based cuttings to prepare low-density, high-strength, high-acid-resistant environmentally friendly ceramsite proppants for oil and gas re-exploitation is an effective way to realize the resource utilization of oil-based cuttings and increase oil and gas production.

[0005] CN116177881A discloses an ultra-low density ceramsite fracturing proppant and its preparation method. The preparation method is as follows: calcining the oil-based rock cuttings dry residue to obtain calcined dry residue; mixing the calcined dry residue with quartz sand tailings and ball milling to obtain a mixture; using water as a medium, granulating the mixture into balls to obtain green balls; drying the green balls, and then sintering them at a gradient temperature to obtain sintered mature balls; cooling the sintered mature balls and screening them. The method calcines the oil-based rock cuttings as raw materials, and then prepares the ultra-low density ceramsite fracturing proppant through low-temperature gradient sintering. CN117843348A discloses a low-density high-strength petroleum ceramsite proppant, including: drilling rock cuttings, secondary aluminum ash, bauxite and methyl cellulose, which is prepared by subjecting the drilling rock cuttings and secondary aluminum ash to light calcination and then batching, mixing, granulating and calcining. In the above schemes, in order to obtain low-density fracturing proppants, the raw materials need to be pre-calcined, which will lead to complex processes, high energy consumption, and increased production costs. Summary of the invention

[0006] The purpose of the present invention is to solve the above technical problems and provide a method for preparing an oil-based cuttings-based fracturing proppant with simple process, low energy consumption and low production cost.

[0007] The present invention also provides an oil-based cuttings-based fracturing proppant prepared by the above method and having low density, high strength and high acid resistance.

[0008] The preparation method of the oil-based rock cuttings-based fracturing proppant of the present invention comprises the following steps: crushing the dried oil-based rock cuttings and bauxite respectively, passing through a 60-mesh sieve, mixing to obtain a mixture, adding water to the mixture to granulate to obtain a raw material ball; calcining the raw material ball in a tubular furnace under anaerobic conditions, and cooling to obtain the fracturing proppant.

[0009] The drying temperature of the oil-based rock cuttings is 40-60° C., and the drying time is 10-15 hours. The drying temperature of the bauxite is 105° C., and the drying time is 4-6 hours.

[0010] The mass ratio of the oil-based rock cuttings to bauxite is (3:7) to (5.5:4.5), and the oil content in the mixture is 5% to 10% by mass.

[0011] The mixed material is granulated after nickel oxide powder is added into the mixed material.

[0012] The molar ratio of iron to nickel in the mixture after adding nickel oxide powder is controlled to be 1-2:1.

[0013] The mixed material is ball-milled in a vacuum ball mill for 2-5 hours.

[0014] The particle size of the mixed material after ball milling is controlled to pass through a 140-mesh sieve, and the material on the sieve is less than 3wt%.

[0015] The particle size of the raw material balls obtained after granulation is controlled to be 40-140 mesh.

[0016] The calcination conditions of the raw material ball are: keeping at 500-800°C for 1-2 hours under anaerobic conditions, and then calcining at 1170-1300°C for 1-2.5 hours.

[0017] The oil-based rock cuttings-based fracturing proppant of the present invention is prepared by the above preparation method.

[0018] In view of the problems existing in the background technology, the inventor has made the following improvements:

[0019] 1) The raw materials are only dried without calcining, which saves the energy consumption of high-temperature calcination, removes only free water, and deliberately retains the oil in the oil-based rock cuttings, thereby achieving the purpose of retaining the carbon source for the generation of carbon nanotubes.

[0020] 2) Different from the ventilation calcination of existing fracturing proppants, the present invention adopts anaerobic calcination in the calcination step, uses low-grade bauxite and oil-based rock cuttings, and calcines at high temperature to generate corundum and mullite. Based on the principle of chemical vapor deposition under an anaerobic environment, the pyrolysis gas of organic matter in the oil-based rock cuttings is used as a carbon source, and the iron in the raw material is used as a catalyst to form a carbon nanotube structure on the surface of the mineral phase. The strength and hardness of the ceramsite proppant are significantly improved by using its unique structure and mechanical properties, while also having a low density. The carbon nanotubes can maintain the stability of their structure and good mechanical properties in corrosive media such as acidic, alkaline, and salt solutions, so they can protect part of the mineral phase from acid erosion, so that the ceramsite proppant has the multiple functions of low acid solubility. Preferably, the calcination conditions are controlled as follows: in anoxic conditions, keep warm at 500-800°C for 1-2h, so that the pyrolysis gas grows carbon nanotubes on the proppant under the action of the catalyst, and then calcine at 1170-1300°C for 1-2.5h to ensure that components such as silicon and aluminum generate high-strength corundum phase and mullite phase to ensure the basic strength of the proppant. If the high-temperature calcination time is too long, the high-strength corundum phase and mullite phase that have been generated will melt under the action of low-melting-point substances and generate relatively low-strength substances with other components, while if the high-temperature calcination time is too short, the synthesis amount of high-strength corundum phase and mullite phase will be insufficient, thereby affecting the quality of the product.

[0021] 3) Nickel oxide is added as a catalyst. The addition of nickel can not only promote the production of carbon nanotubes, but also inhibit the generation of phases with poor acid resistance. The iron in the raw material can increase the production of carbon nanotubes. The two work together to increase the active sites of the catalyst, improve the catalytic efficiency, and more carbon source gas can be decomposed and converted into carbon nanotubes, which is particularly beneficial to the growth of carbon nanotubes, thereby improving the strength and acid resistance of the proppant. The preferred molar ratio of iron / nickel is 1-2 to ensure the growth and stable performance of carbon nanotubes. Too high an amount of nickel added may lead to an increase in structural defects of carbon nanotubes, such as bending and breaking, which will destroy the integrity of carbon nanotubes, thereby reducing their mechanical strength. Too low an amount will lead to insufficient catalytic activity, which will reduce the growth rate of carbon nanotubes and even fail to form a complete carbon nanotube structure.

[0022] 4) The mixed materials are ball milled and mixed in a vacuum ball mill. While meeting the particle size requirements, the grinding body is used under vacuum conditions to make the materials fully contact and mix, and at the same time, direct contact between oxygen and oil-based rock chips can be avoided, thereby preventing the occurrence of oxidation reactions to ensure the synthesis of carbon nanotubes. The ball ink tank is preferably made of polytetrafluoroethylene, and the ball milling time is 2-5 hours.

[0023] The invention uses low-grade bauxite and oil-based rock cuttings as raw materials, nickel oxide as a catalyst, and prepares a fracturing proppant through vacuum mixing, granulation and anaerobic calcination steps. The process route is simple, the cost is low, the energy consumption is low (reduced by 20%-30% energy consumption), the firing temperature range is wide, and it is easy to control, and the problems of under-burning and over-burning can be avoided as much as possible. The prepared fracturing proppant has the advantages of low density, high strength and high acid solubility. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The following percentages are all mass percentages. Among them, the bauxite comes from a bauxite mine in Chongqing, and the oil-based rock cuttings come from a shale oil field in Chongqing.

[0025] Embodiment 1:

[0026] The steps include:

[0027] (1) Bauxite is dried at 105°C for 4 hours for use, and oil-based rock cuttings are dried at 40°C for 15 hours to remove free water in the raw materials.

[0028] (2) The oil-based rock cuttings and bauxite dried in step (1) are crushed and passed through a 60-mesh sieve, and mixed in a ratio of 3:7 to obtain a mixture having an oil content of 5 wt %.

[0029] (3) Adding a certain amount of nickel oxide powder to the mixture of step (2) so that the molar ratio of iron to nickel in the raw materials after the matching is 1; then ball milling the raw materials with the matching number in a vacuum ball mill for 2 hours, and the particle size of the mixed material after ball milling exceeds a 140-mesh sieve, and the sieve-surface material is less than 3wt%.

[0030] (4) taking the mixture of step (3) and granulating it in a round pot granulator by spraying water to obtain raw material balls of 40 / 70 mesh and 40-140 mesh;

[0031] (5) The raw material balls obtained in step (4) are calcined in a tubular furnace, kept at 500° C. for 1 hour under anaerobic conditions, and then calcined at 1300° C. for 1 hour. After cooling, a low-density, high-performance, environmentally friendly fracturing proppant is obtained.

[0032] Embodiment 2:

[0033] The steps include:

[0034] (1) Bauxite is dried at 105°C for 6 hours for use, and oil-based rock cuttings are dried at 60°C for 10 hours to remove free water in the raw materials.

[0035] (2) The oil-based rock cuttings and bauxite dried in step (1) are crushed and sieved through a 60-mesh sieve, and mixed in a ratio of 5.5:4.5 to obtain a mixture having an oil content of 15 wt %.

[0036] (3) Add a certain amount of nickel oxide powder to the mixture of step (2) so that the molar ratio of nickel to iron is 2; then, the raw materials with the matching number are ball-milled in a vacuum ball mill for 5 hours, and the particle size of the mixture after ball milling exceeds a 140-mesh sieve, and the sieve-surface material is less than 3wt%.

[0037] (4) taking the mixture of step (3) and granulating it in a round pot granulator by spraying water to obtain raw material balls of 40 / 70 mesh and 40-140 mesh;

[0038] (5) The raw material balls obtained in step (4) are calcined in a tubular furnace at 800° C. for 2 h under anaerobic conditions, and then calcined at 1170° C. for 2.5 h. After cooling, a low-density, high-performance, environmentally friendly fracturing proppant is obtained.

[0039] Embodiment 3:

[0040] The steps include:

[0041] (1) Bauxite is dried at 105°C for 5 hours and the oil-based rock cuttings are dried at 50°C for 12 hours to remove free water from the raw materials.

[0042] (2) The oil-based rock cuttings and bauxite dried in step (1) are crushed and passed through a 60-mesh sieve, and mixed in a ratio of 4:6 to obtain a mixture having an oil content of 10 wt %.

[0043] (3) Add a certain amount of nickel oxide powder to the mixture of step (2) so that the molar ratio of nickel to iron is 1.5; then, the raw materials with the matching number are ball-milled in a vacuum ball mill for 4 hours. After ball milling, the particle size of the mixture passes through a 140-mesh sieve, and the sieve material is less than 3wt%.

[0044] (4) taking the mixture of step (3) and granulating it in a round pot granulator by spraying water to obtain raw material balls of 40 / 70 mesh and 40-140 mesh;

[0045] (5) The raw material balls obtained in step (4) are calcined in a tubular furnace at 700° C. for 1.5 h under anaerobic conditions, and then calcined at 1200° C. for 2 h. After cooling, a low-density, high-performance, environmentally friendly fracturing proppant is obtained.

[0046] Comparative Example 1:

[0047] Compared with Example 3, the difference is that the calcination process is completed under air conditions, and the rest is the same as Example 3.

[0048] Comparative Example 2:

[0049] Compared with Example 3, nickel oxide is not added, and the rest is the same as Example 3.

[0050] Comparative Example 3:

[0051] Compared with Example 3, after adding nickel oxide powder, a common ball mill is used to mix and then granulate. The rest is the same as Example 3.

[0052] Comparative Example 4:

[0053] A low-density ceramsite proppant produced by a company in Gongyi, Henan using low-grade bauxite as raw material was selected.

[0054] The test results are as follows:

[0055]

[0056]

[0057] Selecting products of the same density for comparison, the crushing rate and acid solubility of Examples 1-3 are significantly lower than those of the comparative example, indicating that the process conditions of the present invention achieve the strengthening effect of the ceramsite proppant. In addition, the heavy metal leaching concentrations of Examples 1-3 are all far lower than the standard value, indicating that the present invention can achieve the harmlessness and resource utilization of oil-based rock cuttings.

Claims

1. A method for preparing an oil-based cuttings-based fracturing proppant, characterized in that: The dried oil-based rock cuttings and bauxite are crushed separately, passed through a 60-mesh sieve, and then mixed to obtain a mixture, and the mixture is granulated with water to obtain a raw ball; the raw ball is calcined in a tubular furnace under anaerobic conditions, and a fracturing proppant is obtained after cooling.

2. The method for preparing the oil-based cuttings-based fracturing proppant according to claim 1, characterized in that: The drying temperature of the oil-based rock cuttings is 40-60° C., and the drying time is 10-15 hours. The drying temperature of the bauxite is 105° C., and the drying time is 4-6 hours.

3. The method for preparing the oil-based cuttings-based fracturing proppant according to claim 1, characterized in that: The mass ratio of the oil-based rock cuttings to bauxite is (3:7) to (5.5:4.5), and the oil content in the mixture is 5% to 10% by mass.

4. The method for preparing the oil-based cuttings-based fracturing proppant according to any one of claims 1 to 3, characterized in that: The mixed material is granulated after nickel oxide powder is added into the mixed material.

5. The method for preparing the oil-based cuttings-based fracturing proppant according to claim 5, characterized in that: The molar ratio of iron to nickel in the mixture after adding nickel oxide powder is controlled to be 1-2:

1.

6. The method for preparing the oil-based cuttings-based fracturing proppant according to claim 1, characterized in that: The mixed material is ball-milled in a vacuum ball mill for 2-5 hours.

7. The method for preparing the oil-based cuttings-based fracturing proppant according to claim 6, characterized in that: The particle size of the mixed material after ball milling is controlled to pass through a 140-mesh sieve, and the material on the sieve is less than 3wt%.

8. The method for preparing the oil-based cuttings-based fracturing proppant according to claims 1-3, characterized in that: The particle size of the raw material balls obtained after granulation is controlled to be 40-140 mesh.

9. The method for preparing the oil-based cuttings-based fracturing proppant according to any one of claims 1 to 3, characterized in that: The calcination conditions of the raw material ball are: keeping at 500-800°C for 1-2 hours under anaerobic conditions, and then calcining at 1170-1300°C for 1-2.5 hours.

10. An oil-based rock cuttings-based fracturing proppant, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Low-density high-strength petroleum ceramsite proppant and preparation method thereof

    CN117843348A